Quality of life in elderly adults from Guerrero, Mexico - Peña-Marcial, Elvia; Bernal-Mendoza, Lorena Inés; Reyna-Avila, Leticia; Pérez-Cabañas, Rodrigo; Onofre-Ocampo, Derly Asmir; Cruz-Arteaga, Ingrid Astrid; Silvestre-Bedolla, Dulce Anel (Universidad y Salud, 2019)
Introduction: Quality of life is defined as a state of social, emotional, spiritual, intellectual and occupational wellbeing. Quality of life allows individuals to properly satisfy their needs and reach a level of adaptation to their own conditions and environments according to their health status, limitations and the support they receive to supplement them. Objective: To describe the quality of life of elderly adults in the State of Guerrero-Mexico, taking into account the social context where they live. Materials and methods: Quantitative research using a cross-sectional and analytical approach. The sample was probabilistic, with 75 adults older than or equal to 65 years of age, who were residents of asylums, day houses or rural areas. The applied selection criterion was their signature of the informed consent form. We used the sociodemographic questionnaire and the Spanish version 2 of the SF-36 Health Survey questionnaire that contains questions grouped within their respective items. Results: 80% of the older adults manifested a poor quality of life. Conclusions: Elderly adults from Guerrero displayed high percentages of physical, emotional and social problems, which ultimately lead to poor health and life perspectives.